2020
DOI: 10.1016/j.jor.2019.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Failure of short versus long cephalomedullary nail after intertrochanteric fractures

Abstract: The aim of study is to examine the frequency of reoperation and difference in failures for short cephalomedullary nail (SN) and long cephalomedullary nail (LN).We included patients with an intertrochanteric fracture treated with Gamma nail (Stryker®). All radiographs were reviewed, TAD and diastasis were measured, and type of failure registered.216 patients were included, 95 short nails and 121 long nails. We found 12 reoperations, 5 in the SN group and 7 in the LN group. Most common failure was cut out. Our s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…Peri-implant infection rates 1-year post-operatively were also reported to be similar in the 6 studies which reported on them 18 , 20 , 24 , 26 , 32 , 33 .…”
Section: Resultssupporting
confidence: 74%
See 3 more Smart Citations
“…Peri-implant infection rates 1-year post-operatively were also reported to be similar in the 6 studies which reported on them 18 , 20 , 24 , 26 , 32 , 33 .…”
Section: Resultssupporting
confidence: 74%
“…1-year complication rate was reported in 11 studies, with only Li et al . reporting statistically fewer incidences in the long CMD group 12 , 18 , 21 23 , 26 28 , 30 , 32 , 33 .…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…Relation between trochanteric and femoral neck fractures, as a type of osteoporotic hip fractures too, is variable in different parts of the world, confirming the influence of genetic and environmental factors in their incidence. Femoral neck fractures are more present in Northern Europe, while trochanteric fractures are more occurred in Central and Southern Gold standard in trochanteric fractures internal fixation is third generation of Gamma Nail, as an intramedullary method with a cannulated lag screw 6,7,8,9 . Trochanteric fractures with pertrochanteric component (fracture line extending in lower-medial direction from the greater trochanter) require the use of lag screws 6,9 .…”
Section: Introductionmentioning
confidence: 99%